PENGARUH KEPUASAN KERJA DAN SELF EFFICACY SERTA SELF ESTEEM TERHADAP KINERJA KARYAWAN PT. GRAHA MANDALA SAKTI BONTANG - Muhammad Hidayat; Sukisno S. Riadi; Triana Fitriastuti (Jurnal Ilmu Manajemen Mulawarman (JIMM), 2017)
The purpose of this study was to determine the influence of job satisfaction and self efficacy as well as self esteem on employee job job performance. This research was conducted at the Office of PT. Graha Mandala Sakti Bontang sampling method using purposive sampling, with commissioners and managers do not include the amount of the population used as many as 250 people and collected samples of 80 people on the employee stay with the work 1 year. The data in this study using primary data, questionnaires. Hypothesis test used in this study is Multiple Linear Regression using SPSS version 22. The results of this study show that: 1) Job satisfaction has a positive and significant effect on employee job performance at the office of PT. Graha Mandala Sakti Bontang, 2) Self efficacy has a positive and significant effect on employee job performance at the office of PT. Graha Mandala Sakti Bontang, 3) Self esteem has a positive and significant effect on employee job performance at the office of PT. Graha Mandala Sakti Bontang,Keywords: job satisfaction, self efficacy, self esteem, and job performance.